Thiol regulation by Mn porphyrins, commonly known as SOD mimics - Batinic-Haberle, Ines (Redox Biol, 2019)
Superoxide dismutases play an important role in human health and disease. Three decades of effort have gone into synthesizing SOD mimics for clinical use. The result is the Mn porphyrins which have SOD-like activity. Several clinical trials are underway to test the efficacy of these compounds in patients, particularly as radioprotectors of normal tissue during cancer treatment. However, aqueous chemistry data indicate that the Mn porphyrins react equally well with multiple redox active species in cells including H(2)O(2), O(2)(•-), ONOO(-), thiols, and ascorbate among others. The redox potential of the Mn porphyrins is midway between the potentials for the oxidation and reduction of O(2)(•-). This positions them to react equally well as oxidants and reductants in cells. The result of this unique chemistry is that: 1) the species the Mn porphyrins react with in vivo will depend on the relative concentrations of the reactive species and Mn porphyrins in the cell of interest, and 2) the Mn porphyrins will act as catalytic (redox cycling) agents in vivo. The ability of the Mn porphyrins to catalyze protein S-glutathionylation means that Mn porphyrins have the potential to globally modulate cellular redox regulatory signaling networks. The purpose of this review is to summarize the data that indicate the Mn porphyrins have diverse reactions in vivo that are the basis of the observed biological effects. The ability to catalyze multiple reactions in vivo expands the potential therapeutic use of the Mn porphyrins to disease models that are not SOD based.